The traditional ritual culture of the Kazakhs as the philosophy and essence of the work of modern choreographers (Journal of Philosophy Culture and Political Science, 2019)
Abstract. The article considers new approaches of Kazakhstani choreographers in creating choreographic works based on the material of the traditional and ritual culture of the ethnos in the synthesis of modern and national plastics. The appeal of modern choreographers to the origins and ritual culture of an ethnic group in Kazakhstan’s art criticism is a new vector for the preservation of national traditions insociety. Thus, a primitivedance was born, which evolved into a real way of communication and manifestation of feelings and spiritual culture of an ethnos. At the present stage of development of national choreography in Kazakhstan, professional competitions of Kazakh dance are held, each of which opens up new names for performers and directors choreographers. The aim of the study is to identify new directionsand trends in the development of Kazakh dance, where unique plastic and aesthetic ideals recreate the ancient Kazakh culture and ethos philosophy based on the example of the creative activity of the leading choreographic groups of Kazakhstan. Key words: traditional culture, Kazakh dance, Neokazakh choreography, ethnos spiritual culture, choreographic art, dance traditions.